2004
DOI: 10.1136/oem.2003.012427
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic sensitisation to grapes in a sample of workers in the wine industry: Table 1

Abstract: Aims: To assess the prevalence of sensitisation to grapes (Vitis vinifera var. agiorghitiko) in a population with repeated exposure to grape allergens through direct cutaneous contact as well as through the gastrointestinal tract. Methods: One hundred and twenty subjects were enrolled in each of four groups: grape harvesters, winery workers in selection of grapes, winery workers operating de-stemming/ crushing/pressing machines, and administrative personnel. Sensitisation to grapes was examined by skin prick-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is also evident that the commonly held view that the grape mould (B. cinerea) is an important allergen in grape handling is not borne out by the findings in this study [24]. The contribution of grape allergen or vine pollen sensitisation to allergic symptoms is another factor to consider in explaining the allergic symptoms reported [15, 25]. This, however, was not assessed since no well-validated SPT extracts were available at the time of the study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is also evident that the commonly held view that the grape mould (B. cinerea) is an important allergen in grape handling is not borne out by the findings in this study [24]. The contribution of grape allergen or vine pollen sensitisation to allergic symptoms is another factor to consider in explaining the allergic symptoms reported [15, 25]. This, however, was not assessed since no well-validated SPT extracts were available at the time of the study.…”
Section: Discussionmentioning
confidence: 65%
“…The farming of wine and table grapes is one of the largest fruit industries in the Western Cape, employing about 50,000 workers in approximately 3,000 farms [14]. Vineyards in contrast to other fruit farms (citrus, apple and pear) have not been previously investigated for occupational allergy and asthma due to spider mites, although sensitisation to grapes has recently been studied [15]. Since these vine farms are located within the same geographical region as apple farms, the ecological distribution of spider mites in these vineyards was considered in all likelihood to be very similar to apple farms.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of sensitization to grape plant materials was beyond the scope of the present study. A recent study on sensitization to grapes among Greek grape workers has shown that asymptomatic sensitization to grapes was high and that workers handling grapes were more likely than those inhaling must vapors or controls to present sensitization [Kalogeromitros et al, 2004]. Further studies are needed in order to measure sensitization to grapes among grape farmers in Crete and possible cross-reactions of Cretan grape varieties with other plant allergens.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, allergen‐microarrays were validated against the CAP/radioimmunoallergosorbent test (RAST) system with sera from sensitized patients in a routine diagnostic setting (13, 15). However, it is well known that not all patients with sIgE do suffer from clinically relevant allergies (16–19). Hence, only the combination of the patient's history with in vivo and in vitro tests allows the estimation of the clinical relevance of allergen sensitization.…”
mentioning
confidence: 99%